Theoretical study on the electronic structure of NaS including spin-orbit coupling. (March 2021) - Liu, Yadong; Li, Rui; Liu, Yahong; Liu, Yong; Xue, Jianlei; Yan, Bing
Highlights: The SOC and CV effects are included in our MRCI+ Q calculation of NaS. Potential energy curves and spectroscopic constants of Λ-S and Ω states are evaluated. Predissociation and perturbations for A 2 Σ + state are analyzed. The spontaneous radiative lifetimes of the transitions involving low-lying states are reported. Abstract: The 19 Λ-S states and the low-lying Ω states of NaS molecule are computed by using the multireference configuration method (MRCI) including spin-orbit coupling (SOC), core-valence correlation (CV), scalar relativistic effects and Davidson (+ Q ) correction. The potential energy curves (PECs), spectroscopic constants and dipole moments are obtained. The predissociation mechanism of A 2 Σ + is investigated in detail with aid of the SOC matrix elements. Finally, the transition properties of the NaS molecule including the Franck-Condon Factors (FCFs), transition dipole moments (TDMs), and the spontaneous radiative lifetimes of lower vibrational states are investigated. Our computational results will help to understand the spectroscopic and properties for further experimental studies of NaS.